Relationship of asprosin and diabetes: a meta-analysis - Xiandong Zeng; Xin Sun; Wei He; Jing Xie; Caihong Xin (BMC Endocrine Disorders)
Abstract Background Diabetes characterized by chronic hyperglycemia, has become a serious hazard to human health in the recent decades. Previous research suggests that asprosin may contribute to the development of diabetes by regulating glucose homeostasis, appetite, insulin secretion, and insulin sensitivity. Although some studies have shown that asprosin levels are higher in patients with diabetes than in healthy individuals, the association between asprosin levels and diabetes remains controversial. Aim This meta-analysis aimed to assess asprosin levels in patients with diabetes and in healthy individuals. Methods We searched the following electronic databases: Web of Science, ScienceDirect, PubMed, and Willy. The title or abstract uses the following search term: “diabetes” is used in combination with the term “asprosin.” The meta-analysis results are presented as standardized mean differences (SMDs) with corresponding 95% confidence intervals (CIs). Results Fourteen articles were included in this meta-analysis. In our meta-analysis, the asprosin level in patients with diabetes was significantly higher than that in healthy controls (SMD: 0.95, 95% CI [0.66, 1.24]). Moreover, there was a significant difference in the asprosin levels between patients with diabetes without complication and those with complication (SMD: 0.81, 95% CI [0.33, 1.29]). Conclusions This systematic review is the first to evaluate the relationship between asprosin levels and diabetes. The asprosin levels were significantly higher in patients with diabetes. Clinical trial number Not applicable.